Development of Spare Part Management System for Automotive Repairing Shop - Lau, Zi Jian; Ab.Aziz, Ruhaya (Applied Information Technology And Computer Science, 2022)
Spare part management system is a system that allow an organization to manage the interrelated parts of its business to achieve its objectives. The target organization of this project is Kedai Motor Auto Power, which located at Melaka. Some problems that found from the traditional management system of Kedai Motor Auto Power are data redundancy, limited data sharing and difficulty in accessing data. The objective of this project is to design, develop and evaluate the automotive repairing shop information system. The methodological approach that used for the Spare Part Management System in Kedai Motor Auto Power is Object-Oriented approach. Object-oriented approach is suitable for Spare Part Management System as the system consists many small modules that combined both process and data. The spare part management system provides stock management feature, sales management feature, supplier information feature, search bar feature, login and registration feature in order to solve the problem faced by Kedai Motor Auto Power. Spare Part Management System of Kedai Motor Auto Power should allow the owner to manage the stock and sales of the shop through online. Moreover, the system should also allow the customers to make order of the spare part through online. This system is expected to manage the information and inventory of spare part for the Kedai Motor Auto Power with more systematic way. The contributions of Spare Part Management System is providing a paperless, efficiency and systematic working environment to the owner. These contributions are promoting the better working environment in the future.